Mosby's dictionary of medicine, nursing & health professions (Elsevier/Mosby, 2013)
"So much more than just a bestselling dictionary, Mosby's Dictionary of Medicine, Nursing & Health Professions, 9th Edition is a one-stop reference to help you make sense of the complex world of health care. It features over 56,000 authoritative definitions, 45 appendixes, a color atlas of the human body, online resources, and more than 2,450 full-color illustrations - nearly three times more than any other dictionary available - making it an indispensible reference for students and professionals alike."--Publisher's website.